Primary versus secondary infertility: Epidemiology and characteristics from a referral hospital in Saudi Arabia - Nouf A AlShamlan; Reem S AlOmar; Abdulrahman Abdulrazzaq Alfryyan; Abdulsalam Essam Almuhanna; AlJawhara Raed AlSaadoun; Halah Raaed AlMuhaidib; Mohammad Ghazi Alhaidari; Rakan Saud Alharbi; Abdullah H Alreedy; Nouf A AlTooq; Amani S AlOtaibi (SAGE Open Medicine, 2025)
Objective: This study aimed to explore the epidemiology and characteristics of primary versus secondary infertility cases referred to infertility clinics at a major Saudi Arabian referral hospital, as well as potential correlations between patients’ characteristics and infertility types. Methods: All female patients who visited the infertility clinics between January 2020 and December 2022 were included in this retrospective chart review study. Data were collected on medical histories, medications, diagnostic tests, reproductive characteristics, and the type and cause of infertility. Results: During the study period, a total of 667 female patients attended the infertility clinic. The mean age was 33.64 ± 6.56 years. The mean marriage duration was 79.92 ± 57.17 months, and the mean duration of infertility was 59.80 ± 49.71 months. Of the total patients, 56.07% had secondary infertility, whereas 43.93% had primary infertility. The most frequently defined causes were unexplained, followed by combined factors. Temporal patterns show a gradual, but significant decrease in cases during the COVID-19 pandemic peak months (25.82% reduction between January and April). Results from diagnostic tests were generally normal for most patients. Females with secondary infertility tended to be older (Mean age = 34.64 vs 32.37 years) and had been married for longer (Mean duration 96.18 vs 68.86 months; p -value < 0.001). The duration of infertility was longer for patients with primary infertility. An irregular menstrual cycle was more common in females with the primary type of infertility. Individuals with secondary infertility were significantly more likely to have had previous surgery. Conclusion: Crucial information in the epidemiology of infertility has been found. The older age among secondary infertility, as well as the high proportion of unknown causes warrants further research. Women’s health consultants and family physicians should initiate investigations and manage underlying causes during the waiting period for specialized clinic appointments.